Peningkatan Hasil Belajar Pendidikan Agama Islam - Junaidi, Junaidi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) among fourth-grade students of SD Negeri 15 Malampah Utara through the implementation of the discussion method. The background of this research is the low student learning outcomes due to a lack of active engagement in the learning process. The research method used is Classroom Action Research (CAR) with a cyclical model consisting of planning, implementation, observation, and reflection. The research subjects were 20 fourth-grade students. Data were collected through learning outcome tests, observation sheets, and interviews, and analyzed descriptively. The results indicate that the discussion method significantly improved students' learning outcomes across cycles and enhanced their active participation in the learning process. This study concludes that the discussion method is effective in improving PAI learning outcomes and is recommended for teachers to enhance the quality of education.